2010
DOI: 10.1016/j.molcel.2010.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Hsp12 Is an Intrinsically Unstructured Stress Protein that Folds upon Membrane Association and Modulates Membrane Function

Abstract: Hsp12 of S. cerevisiae is upregulated several 100-fold in response to stress. Our phenotypic analysis showed that this protein is important for survival of a variety of stress conditions, including high temperature. In the absence of Hsp12, we observed changes in cell morphology under stress conditions. Surprisingly, in the cell, Hsp12 exists both as a soluble cytosolic protein and associated to the plasma membrane. The in vitro analysis revealed that Hsp12, unlike all other Hsps studied so far, is completely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
155
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(167 citation statements)
references
References 63 publications
(73 reference statements)
9
155
0
3
Order By: Relevance
“…Thus, in contrast with nonmodified Lti30, phosphorylated Lti30 appears to decrease the fluidity of the lipid bilayer. Notably, this effect is similar to that observed upon membrane association of the disordered heat shock protein HSP12, a LEA-like protein from Saccharomyces cerevisiae (Welker et al, 2010): phosphorylation seems to change Lti30 from a cold shock protein that increases lipid fluidity to a heat shock protein that decreases lipid fluidity. Even if this resemblance may be accidental, the very phenomenon opens the possibility that the role of phosphorylation is to deactivate selectively and gradually the membrane fluidity effect of Lti30 binding.…”
Section: Tuning Of the Membrane Properties By Lti30 Phosphorylationsupporting
confidence: 66%
See 2 more Smart Citations
“…Thus, in contrast with nonmodified Lti30, phosphorylated Lti30 appears to decrease the fluidity of the lipid bilayer. Notably, this effect is similar to that observed upon membrane association of the disordered heat shock protein HSP12, a LEA-like protein from Saccharomyces cerevisiae (Welker et al, 2010): phosphorylation seems to change Lti30 from a cold shock protein that increases lipid fluidity to a heat shock protein that decreases lipid fluidity. Even if this resemblance may be accidental, the very phenomenon opens the possibility that the role of phosphorylation is to deactivate selectively and gradually the membrane fluidity effect of Lti30 binding.…”
Section: Tuning Of the Membrane Properties By Lti30 Phosphorylationsupporting
confidence: 66%
“…Interestingly, our data show that binding of Lti30 to LUVs does not protect against degradation (Figure 9). This behavior contrasts with that of the disordered proteins Vpg and HSP12, which both become protected against degradation upon vesicle association (Rantalainen et al, 2009;Welker et al, 2010). Moreover, we find that proteolytic cleavage of membrane-associated Lti30 leads to dissociation of the vesicle aggregates: the large aggregates disappear gradually as Lti30 is degraded (Figure 9).…”
Section: Luvs Do Not Protect Lti30 Against Protease Degradation But mentioning
confidence: 78%
See 1 more Smart Citation
“…In yeast (Saccharomyces cerevisiae), the knockout and overexpression of two different hydrophilins strongly influences cell survival after desiccation (Dang and Hincha, 2011), whereas the heat shock protein12 protects the cells from heat damage (Welker et al, 2010). In Caenorhabditis elegans, RNAi knockdown of an LEA gene reduces the desiccation tolerance of the animals (Gal et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This comparison leads to the conclusion that the outer membrane mitochondrial porin is possibly an essential part of Y. lipolytica pH-adaptation machinery, independent of the utilized nutrient source. Another identified alkaline-inducible component of Y. lipolytica, Hsp12 is an intrinsically unstructured stress protein that folds upon membrane association and modulates membrane function (Welker et al, 2010 Hsp12, we observed changes in cell morphology under stress conditions. Surprisingly, in the cell, Hsp12 exists both as a soluble cytosolic protein and associated with the plasma membrane.…”
Section: Functions and Genomic Organisation Of The Genes Encoding Potmentioning
confidence: 85%